Neurocardiogenic syncope and associated conditions: insight into autonomic nervous system dysfunction - Antoine Kossaify; Kamal Kallab (KARE Publishing, 2013)
Neurocardiogenic syncope is known to be associated with autonomic nervous system dysfunction, although the mechanism has not been entirely elucidated. In this study, we sought to highlight the pathogenic role of the autonomic nervous system in neurocardiogenic syncope and to review the associated co-morbidities known to have a dysautonomic basis. Herein we discuss migraine, orthostatic hypotension, postural orthostatic tachycardia syndrome, endothelial dysfunction, chronic fatigue syndrome, and carotid sinus hypersensitivity with a focus on the pathogenic role of the autonomic nervous system and any consecutive clinical implications. Other conditions, such as pre-syncopal heart rate acceleration and/or instability and pre-syncopal breathing instability, which occur during a tilt test, are discussed in the same perspective.